Before. During. After: The Impact of COVID-19 on the Psychometrics of Young Professionals (Journal of Organizational Psychology, 2024)
This research presents the real psychometric impacts of the pandemic on young professionals. Human resource policies must be appropriately formulated to maintain healthy and productive employees, balancing corporate and individual needs. The changes in personality type, emotional intelligence, and locus of control were measured from before to during COVID and then again from during until after COVID. While the psychometric changes of males were minor during these periods, women experienced numerous changes during COVID-19 but subsided after the pandemic. Men and women exhibit less conscientious behavior, first manifested during the pandemic but persisted after the pandemic. This research sheds insights into the current reluctance of professionals to abandon remote working instituted during the pandemic and management’s insistence that workers return to the office.
Keywords: organizational psychology; psychometrics; psychometric measure; personality traits; emotional intelligence; locus of control; anxiety; work and social adjustment; COVID-19